2023
DOI: 10.3390/app13074136
|View full text |Cite
|
Sign up to set email alerts
|

Qualitative and Quantitative Evaluation of Multivariate Time-Series Synthetic Data Generated Using MTS-TGAN: A Novel Approach

Abstract: To obtain high performance, generalization, and accuracy in machine learning applications, such as prediction or anomaly detection, large datasets are a necessary prerequisite. Moreover, the collection of data is time-consuming, difficult, and expensive for many imbalanced or small datasets. These challenges are evident in collecting data for financial and banking services, pharmaceuticals and healthcare, manufacturing and the automobile, robotics car, sensor time-series data, and many more. To overcome the ch… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
4
1
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 16 publications
0
4
0
Order By: Relevance
“…The following metrics were used to assess the individual variants obtained by changing the coefficients: Mean Absolute Error (MAE)—The mean absolute error indicates the average difference between the actual and predicted values. The closer the MAE value is to 0, the more appropriate the prediction [ 22 , 23 , 24 ]. where n is the number of values, y i is the measured value, and as a predicted value.…”
Section: Materials Methods and Toolsmentioning
confidence: 99%
See 1 more Smart Citation
“…The following metrics were used to assess the individual variants obtained by changing the coefficients: Mean Absolute Error (MAE)—The mean absolute error indicates the average difference between the actual and predicted values. The closer the MAE value is to 0, the more appropriate the prediction [ 22 , 23 , 24 ]. where n is the number of values, y i is the measured value, and as a predicted value.…”
Section: Materials Methods and Toolsmentioning
confidence: 99%
“…Mean Absolute Error (MAE)—The mean absolute error indicates the average difference between the actual and predicted values. The closer the MAE value is to 0, the more appropriate the prediction [ 22 , 23 , 24 ].…”
Section: Materials Methods and Toolsmentioning
confidence: 99%
“…In an attempt to address the need for large datasets, a recent study introduced an approach with MTS-TGAN, a novel generative adversarial network (GAN) architecture tailored to generate multivariate time-series data closely resembling real-world datasets [26]. The results showed that MTS-TGAN was effective in capturing the distribution and characteristics of real data and potentially reduced errors in predictive and discriminative scores.…”
Section: Temporal Data Generationmentioning
confidence: 99%
“…It is worth noting that healthy production line data are comparatively easier to obtain, since fault conditions are less frequent in regard to their occurrence and documentation; thus, simulated datasets can present a way to train an ML model on exact labeled error conditions or to evaluate an already trained ML model, specifically in the case of anomaly detection where only normal operation data are available [ 16 ]. Furthermore, the acquisition of annotated datasets is especially challenging due to the expenses and time needed for the sensitive task of labeling, since experienced human labor must be involved, and the businesses that have carried through these processes understandably need to keep their data confidential [ 17 ].…”
Section: Introductionmentioning
confidence: 99%